3D interpretation of geological, 3D seismic and conventional geophysical data from the Darlot Gold Mine. Issue 1 (1st December 2019) - Pears, Glenn; Reid, James; McGaughey, John; Turner, Will; Hird, Graeme
Summary: The Darlot gold mine is an Archean orogenic deposit located in the world-class gold and nickel terrain of the Yandal granite-greenstone belt, part of the Yilgarn Craton in Western Australia. A 3D seismic survey centred on the Darlot-Centenary mineralised system was acquired in 2016-2017 with the objective of improving lithological and structural interpretation, and to generally extend understanding of the Darlot 3D mineralised system to support targeting. The capability of modern 3D seismic surveys to image formational contacts and structures in hardrock environments can have a game-changing impact on the effectiveness of brownfields exploration programs because the geometry of mineralised systems can be directly imaged over large volumes of ground. Furthermore, because the formational and structural geometry revealed by 3D seismic also provides the primary control on the physical property variations that magnetic, gravity, and electrical or EM methods respond to, seismic interpretation provides ideal constraints and guidance on the interpretation of other geophysical data. This is particularly valuable when an objective of geophysical interpretation is imaging of second-order controls on physical property variation, such as the effects of alteration. We present the preliminary results of an an integrated geological, petrophysical, seismic and non-seismic geophysical program to effectively support brownfields targeting in hardrock environments.